Menggugat Fungsi Hukum: Ketika Penegak Gadungan Menjadi Pelaku Kejahatan Ekonomi Dan Moralitas - Muhammad Agva Kiansantang (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines a crucial phenomenon within law enforcement in Indonesia, where individuals who should be enforcing the law are instead committing economic crimes and violations of morality. This phenomenon indirectly challenges the function of the law as a primary instrument in realizing justice and social order, due to the abuse of authority and identity by fake law enforcement officers. This study also examines the serious impact of criminal practices committed by fake law enforcement officers on the credibility of legal institutions, the decline of public trust in the justice system, and the weakening of the rule of law in Indonesia. Using a normative juridical approach and case studies, this study also explores the patterns of involvement of fake law enforcement officers in corruption, extortion, abuse of authority, and various violations of professional moral and ethical norms. This study also analyzes how legal loopholes and weaknesses in oversight mechanisms enable these practices, while recommending strategic steps, such as internal reform, strengthening independent oversight, and fair and transparent law enforcement.